Urologist Scores in the Era of the Merit-Based Incentive Payment System (MIPS). Issue 2 (24th March 2022) - Alam, Ridwan; Clifton, Marisa M.; Han, Misop
Abstract: Introduction: The shift from fee-for-service to value-based payment introduces a new set of challenges and opportunities for the practicing physician. It is unknown how urologists have been impacted by the recent implementation of the merit-based incentive payment system (MIPS). We describe the MIPS performance scores of urologists and investigate their association with practice patterns. Methods: Urologists were identified in the 2018 MIPS performance score database and classified by participation status: individual practice, group practice or alternative payment model (APM). The overall MIPS score is comprised of 4 categories: quality, promoting interoperability, cost and improvement activities. Comparative statistics were performed using Tukey's honest significance test and chi-square analysis. Multinomial logistic regression was performed to test associations. Results: A total of 9, 055 urologists were included with the following average scores: quality 82.5, promoting interoperability 88.9, cost 74.4, improvement activities 37.3 and overall 86.9. When stratified by participation status, urologists in group practices scored higher than individual urologists in each category except cost; urologists in APMs often scored even higher. Preference for group practice or APMs was more common among urologists who graduated medical school more recently. Geographic location also appears to be a contributing factor when evaluating practice type. Conclusions: Urologists who participated as a group practice or APM scored higher across most MIPS categories than those in an individual practice. Introduction of a new reimbursement schedule will likely result in further evolution of practice patterns in the future.